Effect of Cu Content on Microstructure and Mechanical Properties for High-Strength Deposited Metals Strengthened by Nano-Precipitation - Jiamei Wang; Chengning Li; Xinjie Di; Dongpo Wang (Metals, 2022)
With the rapid development of low-carbon high strength steel, higher requirements are put forward for the matching welding consumables. The deposited metals with 0.62–2.32% Cu addition was prepared by tungsten inert gas welding via metal cored wire. The effect of Cu element on microstructure and mechanical properties of deposited metals were investigated. The multiphase microstructure of deposited metals consists of bainite, martensite, residual austenite, and martensite-austenite constituents. It is found that Cu decreases the start temperature of martensite (Ms) and enlarges the temperature range of bainite from 372 K to 416 K, improving the formation of bainite. With the increase of Cu content, the fraction of martensite decreases and the shape of M-A constituents changes from strip into granular. There are BCC and FCC Cu precipitates in deposited metals. The diameter of Cu precipitates is 14–28 nm, and the volume fraction of it increases with the increase of Cu content. Meanwhile, the deposited metals with 1.79% Cu can achieve a 10% enhancement in strength (yield strength, 873–961 MPa, ultimate tensile strength, 1173–1286 MPa) at little expense of impact toughness (64.56–56.39 J at −20 °C). Cu precipitation can effectively improve the strength of the deposited metals, but it degrades toughness because of lower crack initiation energy. The deposited metal with 1.79% Cu addition shows an excellent strength-toughness balance.